Biological Properties and Analytical Methods for Micafungin: A Critical Review - Marena, Gabriel Davi [UNESP]; dos Santos Ramos, Matheus Aparecido [UNESP]; Bauab, Taís Maria [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2020)
Micafungin is characterized as one of the most active available drugs for candidemia treatment; however, their use is also associated in prophylaxis protocols in cases of invasive fungal infections. The use of this drug is widely appreciated in the medical field due to be the most active echinocandin available for invasive fungal infections. In order to provide important parameters related to the chemical, physical, biological and therapeutic characteristics, this review article gathers important research results that demonstrate the biological potential of this drug, as well as to present analytical methods that can be used to determine the antifungal potential and a monitoring of administered dosages. Important studies about the methods most commonly used in biological activity evaluation and determination/quantification by analytical methods are provided in this review article. With the data provided, the scientific community will have the possibility to choose the analytical methods and biological that can be employed in clinical and scientific research to provide greater safety and reliability of the results to be found.
Keywords: Analytical methods; antifungal; Echinocandin; Invasive candidiasis; Micafungin